Pengaruh Jenis Kemasan dan Lama Penyimpanan terhadap Serangan Serangga dan Sifat Fisik Ransum Broiler Starter Berbentuk Crumble - Yuli Retnani; Dimar Wigati; Abdul Djamil Hasjmy (Fakultas Peternakan Universitas Jambi, 2009)
Storage of feedstuff is required because development of farm must be made balance with availability of adequate feedstuff. Storage will influence physical properties of feedstuff. Packaging is the one of methods to take care product. Damage by environment can be controlled by packaging. This study was arranged in a Completely Randomize Design with factorial design (4x5) with four replications. The first factor was packaging type (guny sack, plastic sack, paper packaging, and plastic packaging). The second factor was storage (0, 2, 4, 6, 8 weeks). The parameters observed were: water content, water activity, particle size, specific density, bulk density, compacted bulk density, angle of repose and insect attack. Data were analyzed using analysis of variance (ANOVA) and differences between treatments were determined with Duncan test. The results showed that packaging type highly significantly affected (p<0.01) the moisture content, water activity, and compacted bulk density. Storage highly significantly affected (p<0.01) the moisture content, water activity, particle size, specific density, bulk density, compacted bulk density, and angle of repose. Insect attack was increase on guny sack, especially at four weeks of storage. Paper packaging and plastic packaging can take care feedstuff from insect attack until eight weeks, but plastic sack until four weeks, and guny sack until two weeks. Guny sack, plastic sack, paper packaging, and plastic packaging can take care physical properties of feedstuff until eight weeks.